PENGARUH PEMBERIAN MULSA ORGANIK DAN SAAT PEMBERIAN PUPUK NPK 15:15:15 TERHADAP HASIL TANAMAN BABY BUNCIS (Phaseolus vulgaris, L.) VARITAS PERANCIS - Yoppy Sagita Susiawan; Hadi Rianto; Yulia Eko Susilowati (JURNAL VIGOR, 2018)
The research about the effect of giving organic mulchand NPK (15:15:15) fertilizing time on Baby Buncis (Phaseolus vulgaris, L.) France varieties was carried out on January 26rd until March 28rd, 2017. The location of this research was carried at Windusari Village, Windusari District, Magelang Regency. The altitude of location is 450 meters above sea level and the soil type is latosol with pH of 6,8. The experiment was conducted by using a factorial (3x3) that was arranged in a complete randomized block design, repeated three times. The first factor is mulch kind:no mulch, straw and bamboo leaf. The second factor isNPK (15:15:15) fertilizing time: 5 and 10 ; 10 and 15 ; 15 and 20 days after planting. The result of the research shows that straw mulch givesa lot of number of pods per plant, havier fresth weight of pods per plant and longer height of pod per plant. NPK (15:15:15) fertilizing time which at 15 and 20 days after planting gives longer length of pod per plant. Baby Buncis plant shows the same response on mulch kinds at different NPK (15:15:15) fertilizing time.